Impacts of State Paid Family Leave Policies for Older Workers with Spouses or Parents in Poor Health - Breno Braga; Barbara A. Butrica; Stipica Mudrazija; H.E. Peters (Institute of Labor Economics (IZA), 2022)
Since 2004 six states plus Washington, DC have implemented laws that provide paid leave benefits to workers caring for family members who have a disability or serious medical condition. Focusing on the most established state programs—California and New Jersey—this paper investigates whether paid family leave (PFL) policies facilitate greater labor supply, caregiving, and improvements in health outcomes for those likely to provide family care. Using our preferred estimation method, we find that women with a spouse in poor health are 7.4 percentage points more likely to work while providing care after the implementation of PFL compared to those not living in a PFL state. Similarly, women living within 10 miles of a parent in poor health are more likely to work while providing care (5.6 percentage points) after PFL. The implementation of state PFL also leads to improvements in mental health outcomes for these two groups of women. We fail to find strong evidence that PFL affects labor and care decisions for women living more than 10 miles from a parent in poor health. PFL also has less consistent effects on men.
Keywords: I38; J14; J16; 330; family leave; older workers; caregiving